The Analysis of Communication and Coordination of Interprofessional Teams in Sepsis Emergency Management: Analysis of Communication and Coordination of Interprofessional Teams in Sepsis Emergency Management - Sinaga, Patrice Lwy (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Sepsis is a medical emergency that requires a rapid response and effective coordination among healthcare professionals. Communication and interprofessional team coordination play a crucial role in ensuring optimal sepsis management, reducing mortality, and improving patient care quality. This study aims to analyze the effectiveness of communication and coordination within interprofessional teams during emergency sepsis management in healthcare facilities. A qualitative research approach was employed, involving direct observations and in-depth interviews with medical personnel involved in sepsis management. The findings indicate that clear communication, adherence to standardized protocols, and the presence of a competent team leader contribute to effective coordination in emergency situations. However, several challenges were identified, including delayed information transmission, differences in understanding among professionals, and high workload, which may hinder team efficiency. Therefore, strategies to enhance communication and coordination, such as emergency simulation training and the implementation of supportive technologies, are needed to improve the responsiveness of interprofessional teams in sepsis management